Transcending the self to transcend suffering - Ge, Brian H.; Yang, Fan (Frontiers in Psychology, 2023)
Suffering is inevitable in human life. Our perspective paper theorizes on precise mechanisms for how self-transcendence––the state in which an individual looks beyond the self and adopts a larger perspective including concern for others and the world––may help people endure the experience of suffering. From an examination of empirical literature ranging from social psychology to clinical research, we propose three psychological levels on which self-transcendence may aid in transcending suffering: (1) On the level of affect, the unique profundity and positivity of self-transcendent experiences (e.g., awe, flow, compassion) may supersede and reduce the salience of negative affect arising from suffering (e.g., fear, despair, depressive mood). (2) On the level of cognition, the larger frame of reference provided by self-transcendent thinking may contextualize one’s suffering as something comprehendible, thereby helping to resolve the challenges of making meaning from suffering (e.g., that one’s existing meaning systems are unable to explain the suffering event). (3) On the level of motivation, the drive to fulfill one’s need for self-transcendence may counterbalance the more hedonically-oriented motivations that can promote negative coping strategies in response to suffering (e.g., avoidance, substance abuse). All three mechanisms may also provoke downstream prosocial behaviors that help embed the individual into networks of social support. Altogether, by synthesizing specific mechanisms from affective, cognitive, and motivational self-transcendent processes, our paper establishes a theoretical framework for how self-transcendence may help people endure and transcend suffering, thereby elevating the conditions and experiences of our existence.